Evaluation of Challenging Areas of Accrual Accounting Implementation in the Public Sector - Ahmad Mahdavi; Ali Zabihi; Abassali Pouraghajan (مطالعات تجربی حسابداری مالی, 2023)
The purpose of this research is evaluation of the challenging areas of implementation of accrual accounting in the General Department of the Ministry of Economy and Finance of Mazandaran Province. The methodology of this study is mixed, so that in the qualitative part, through systematic screening, the challenging areas of accrual accounting implementation in the public sector are identified. Then, during two stages of Delphi analysis, an attempt is made to check the reliability of the identified dimensions. Finally, in the quantitative part, through interpretive ranking analysis, it seeks to evaluate the areas identified in the context of the General Department of the Ministry of Economy and Finance of Mazandaran province. The results of the study in the qualitative part indicated the existence of 9 challenging areas for the implementation of accrual accounting in the public sector, and during the process of fuzzy Delphi analysis, 8 criteria were confirmed as the reasons for the gap in the implementation of accrual accounting. Then, in the quantitative part, it was determined that the challenge of applying accounting standards of the public sector is an effective factor in creating a gap in the implementation of accrual accounting in the General Department of the Ministry of Economy and Finance of Mazandaran province.